Preparation method and application of zirconium-based oxide adsorption material
Zirconium-based oxide adsorption materials prepared through high-pressure hydrothermal reaction solve the problem of low fluorine removal rate of existing TiO2 materials, improve the adsorption effect on fluorine, selenium, arsenic and heavy metals, and achieve efficient water pollution removal.
Patent Information
- Application Number
- CN202411710231.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing TiO2 adsorbent materials have poor removal rate of fluorine, and the specific surface area and adsorption activity of zirconium-based oxides need to be improved to more effectively remove contaminants in water.
Zirconium oxide chlorine, cerium salt and iron salt are used as precursors to prepare zirconium-based oxide adsorption materials through high-pressure hydrothermal reaction and co-precipitation processes, and the molar ratio and process conditions are optimized to improve specific surface area and adsorption activity.
The prepared zirconium-based oxide adsorption materials have significantly improved the adsorption effect of fluorine, selenium, arsenic and heavy metals, with a removal rate of up to more than 95%, and are suitable for the purification of groundwater and industrial wastewater.
Smart Images

Figure CN119258975A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adsorbent preparation, and in particular relates to a preparation method and application of a zirconium-based oxide adsorption material. Background Art
[0003] The adsorption method is to use the porous structure of the material to physically adsorb the pollution source in the polluted water. Due to its low cost, simple preparation process, and reusability, it is an important technology for removing groundwater pollution. Among them, the mainstream adsorption and filtration material is TiO2. TiO2 material shows a better adsorption effect on pollution such as arsenic, but the removal rate of fluorine is poor. For example, the Chinese patent (CN107746073A) discloses a method for preparing granular titanium dioxide and lanthanum-loaded granular titanium dioxide, which uses titanyl sulfate as a titanium dioxide precursor, adds lanthanum nitrate during the hydrolysis of titanyl sulfate, and prepares granular titanium dioxide and lanthanum-loaded granular titanium dioxide by co-hydrolysis and extrusion spheronization. Microcrystalline cellulose and hydroxypropyl methylcellulose are added during the preparation process to shape the particles, and their strength is increased by extrusion in a granulator, and finally a granular titanium dioxide material with high adsorption activity and mechanical strength and a lanthanum-loaded granular titanium dioxide composite material are obtained. However, even after lanthanum modification, its maximum adsorption capacity for fluorine is only 7.2 mgF / g. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a preparation method and application of a zirconium-based oxide adsorption material, which is prepared by hydrothermal reaction and co-precipitation with a certain proportion of zirconium oxychloride, cerium salt and iron salt as precursors. Not only is the preparation process simple and convenient for large-scale production, but the prepared zirconium-based composite oxide adsorption material has excellent adsorption effect on fluorine, selenium, arsenic and heavy metals, which is of great significance for improving water pollution.
[0005] The first aspect of the present invention aims to provide a method for preparing a zirconium-based oxide adsorption material, comprising the following steps: using a mixed solution of zirconium oxychloride, cerium salt and iron salt as a precursor, obtaining a precipitate through a high-pressure hydrothermal reaction, and preparing the zirconium-based oxide adsorption material after washing and calcining the precipitate after centrifugation; wherein the molar ratio of the zirconium oxychloride, cerium salt and iron salt is 100:(3-6):(8-12).
[0006] The present invention obtains a composite adsorption material through the process steps of high-pressure hydrothermal reaction of a precursor solution, coprecipitation and calcination. The adsorption material is based on zirconium oxide and loaded with a certain amount of nano-scale cerium oxide and iron oxide, and has excellent specific surface area and adsorption activity. Among them, zirconium oxide has a high specific surface area and a special stacking structure, and the oxygen-containing functional groups can provide a large number of adsorption sites, thereby effectively adsorbing pollutant ions, and the surface-loaded nano-cerium oxide and iron oxide play a synergistic role in promoting the adsorption. In addition, zirconium oxide has stable chemical properties and has high selective adsorption of fluoride ions, which makes it perform well in removing fluoride pollution in water.
[0007] More preferably, the molar ratio of the zirconium oxychloride, the cerium salt and the iron salt is 100:(5-6):(9-10).
[0008] Preferably, the cerium salt includes but is not limited to cerous nitrate, cerium nitrate, cerium sulfate or cerium chloride; wherein since the solubility of cerium nitrate and cerium sulfate is greater than that of cerium chloride, the cerium salt is preferably cerium nitrate or cerium sulfate.
[0009] Preferably, the iron salt includes but is not limited to ferric chloride, ferric sulfate or ferric nitrate.
[0010] Preferably, zirconium oxychloride is added in the form of ZrOCl2·8H2O, and the dosage ratio of ZrOCl2·8H2O to solvent water is (1-5) g: (10-50) mL.
[0011] More preferably, the usage ratio of ZrOCl2·8H2O to solvent water is 1.5 g:20 mL.
[0012] In a preferred embodiment, the conditions of the high-pressure hydrothermal reaction are: temperature 180-210° C., time 8-12 h, and heating rate 10-30° C. / min.
[0013] Further preferably, after experimental verification, the optimal hydrothermal temperature is 200°C, the optimal heating rate is 30°C / min, and the hydrothermal reaction time is 10h; therefore, the conditions of the high-pressure hydrothermal reaction are preferably: temperature 200°C, time 10h, heating rate 30°C / min.
[0014] Preferably, the calcination conditions are: first drying at 60-80° C. for 6-10 hours, and then calcining at 260-350° C. for 3-6 hours.
[0015] Preferably, the calcination temperature is 300° C. and the calcination time is 4 hours.
[0016] Preferably, the calcination atmosphere is air atmosphere.
[0017] The second aspect of the present invention aims to provide a zirconium-based oxide adsorption material prepared by the above-mentioned preparation method.
[0018] The third aspect of the present invention aims to provide the use of the above-mentioned zirconium-based oxide adsorbent material in the adsorption and removal of heavy metal, selenium, arsenic or fluorine pollution in groundwater, surface water or industrial wastewater.
[0019] Preferably, the heavy metal is cadmium.
[0020] The present invention has at least the following technical effects:
[0021] The zirconium-based oxide adsorption material of the present invention can effectively remove arsenic and fluorine pollutants in drinking water and heavy metal pollution such as selenium and chromium caused by industrial pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0023] Figure 1 This is a scanning electron microscope (SEM) image of the zirconium-based oxide adsorption material prepared in Example 1.
[0024] Figure 2 This is the XPS graph of the zirconium-based oxide adsorption material prepared in Comparative Example 1.
[0025] Figure 3 This is the XRD diagram of the zirconium-based oxide adsorption material prepared in Comparative Example 1.
[0026] Figure 4 This is the N2 adsorption-desorption curve of the zirconium-based oxide adsorbent material prepared in Example 1.
[0027] Figure 5 It is the removal efficiency of the zirconium-based oxide adsorption material prepared in Example 1 for arsenic, fluorine, selenium and chromium.
[0028] Figure 6 Adsorption isotherms and Langmuir fitting results of the zirconium-based oxide adsorption material prepared in Example 1 for arsenic, fluorine and selenium. DETAILED DESCRIPTION
[0029] Implementable methods that have been discovered in this field. Groundwater pollution includes heavy metal pollution, as well as fluorine, selenium, arsenic and other pollution. Taking fluorine pollution as an example, fluorine is an industrial heavy metal widely used in the preparation of fluorination reagents and fluxes in metal smelting. It is located in the second period of the periodic table, VIIA group, with an atomic number of 9 and a relative atomic mass of 19.00. Most of the fluorine in nature is in a combined state, mainly including: fluorite (CaF2), fluoroapatite [Ca5(PO4)3F], cryolite (Na3AlF6), etc. They are all important chemical raw materials, widely used in aluminum smelting, phosphate fertilizer, steel and organic fluorine high-grade lubricants, rocket propellant oxygen difluoride, hydrazine fluoride and other industrial production. Fluorine-containing wastewater from industries such as electroplating and metal processing, as well as washing water from fluorine-containing waste gas treated by washing method, will cause water and soil pollution after being discharged into the environment. Fluorine-containing smoke and dust settling or leaching by precipitation will pollute soil and groundwater. Fluorine in the human body comes directly from drinking water, food and air. Fluorine is one of the trace elements necessary for the human body. Trace amounts of fluorine can promote children's growth and development and prevent tooth decay. The daily fluoride intake for adults is generally 1.0 to 1.5 mg. Excessive intake will harm health. There are more than 20 forms of fluoride in groundwater, and the proportion of its occurrence forms changes with the properties and chemical composition of the water medium. In neutral or alkaline (pH = 7 to 8) shallow groundwater, there are only 10 forms of fluoride components, namely F, BF(OH)3 - , HFaq, CaF + MgF + , MnF + 、AlF2 + 、AlF2 + , AlF3 and AlF4 - Among them, F, MgF + , CaF + There are three main forms. Generally, F accounts for 79% to 96% of TF (total fluorine concentration), followed by MgF and CaF, which account for 3.1% to 19.2% and 0.3% to 3.0% of TF respectively. The chemical environment of groundwater varies from place to place. If it contains CO3 2- PO4 3- , organic matter and other substances will affect the removal effect of fluoride, so it is very important to choose a defluoridation method suitable for local conditions. Fluoride is one of the trace elements necessary for human life activities. It is a normal component of bones and teeth, necessary for the formation of enamel, and has a protective effect on osteoporosis. However, like other elements, both excessive and insufficient fluoride are harmful to human health. Excessive fluoride can lead to fluorosis, which manifests as systemic chronic damage mainly to teeth and bones.
[0030] The feasible methods have been found in this field. Therefore, groundwater purification technology is very important for drinking water safety. At present, there are mainly the following groundwater treatment technologies at home and abroad:
[0031] 1. Extraction and treatment (P&T) technology is the earliest groundwater pollution remediation technology and a representative technology for ex situ groundwater remediation. Since the groundwater pollution remediation began in the 1980s, groundwater pollution control is still mainly based on P&T technology. The traditional P&T technology is to extract the contaminated groundwater and then treat it on the ground. In recent years, with the continuous deepening of pollution control research, this technology has a broader meaning. As long as groundwater is extracted or injected during the groundwater pollution control process, it is classified as P&T technology.
[0032] 2. Monitoring Natural Attenuation Remediation Technology MNA technology appeared relatively late and was not officially used for groundwater pollution control until the 1990s. This technology is based on the physical and chemical conditions of the contaminated site and the natural attenuation capacity of pollutants to carry out pollution remediation, thereby achieving the purpose of reducing pollutant concentration, toxicity and mobility. In addition, MNA technology must also use corresponding monitoring and control technologies according to the control objectives of the contaminated area to monitor and evaluate the natural remediation process of groundwater.
[0033] 3. In-situ remediation technology. In recent years, the rise of in-situ groundwater remediation technology has attracted widespread attention. Typical in-situ groundwater remediation technologies include: air injection (Air Sparging) remediation technology (AS technology for short), permeable reactive barrier (Permeable Reactive Barrier) remediation technology (PRB technology for short), in-situ biological (Bioremediation) remediation technology, multi-phase extraction (Multi2Phase Extraction) remediation technology, in-situ chemical remediation (ChemicalTreatment) technology, phytoremediation (Phytoremediation) technology and remediation technology combining multiple methods.
[0034] 4. Hydrodynamic control method: Establish a well group control system, change the original hydraulic gradient of groundwater by artificially extracting groundwater or injecting water into the aquifer, and then separate the polluted groundwater from the unpolluted clean water. According to the specific local hydrogeological conditions, it can be divided into the upstream watershed method and the downstream watershed method. The TV equipment of this method is simple, the operating cost is low, it is effective in preventing the spread of pollutants in the early stage of pollution, and the repair efficiency is high, but it is generally used as a temporary control method.
[0035] 5. Physical barrier method: By pouring mortar into the ground, a curtain is formed around the polluted water body to enclose the polluted water body and prevent further spread of pollutants. Such as mud water barrier, vibrating pile water barrier, sheet pile water barrier, block replacement, membrane and synthetic material curtain closure method, etc. The principle is similar to the mortar curtain method, which is to establish a physical barrier underground to isolate the polluted water body.
[0036] 6. Passive collection method: dig a deep enough channel downstream of the groundwater flow, arrange a collection system, collect the pollutants floating on the water surface (such as oil pollutants), or collect all the contaminated groundwater for treatment. This method is more effective in dealing with light pollutants.
[0037] 5. There are also some other technologies, such as in-situ solidification / stabilization technology: by adding solidifiers / stabilizers to the contaminated medium, they react physically and chemically with the pollutants to seal the contaminated soil into a structurally intact solid body with a low permeability coefficient, or convert the pollutants into a chemically inactive form.
[0038] Chemical oxidation / reduction technology: Inject oxidants or reductants into the contaminated area of contaminated soil or groundwater to convert pollutants into non-toxic or relatively less toxic substances through oxidation or reduction.
[0039] Thermal desorption technology: The contaminated soil is heated directly or indirectly to above the boiling point of the target pollutants, causing the pollutants to vaporize, volatilize and separate from the soil particles.
[0040] Soil elution technology: Use physical separation or enhanced elution to separate heavily polluted soil components or transfer pollutants from the soil phase to the liquid phase.
[0041] Cement kiln coordinated disposal technology: Utilizes the high temperature and long-term residence time of gas in the cement rotary kiln to incinerate and solidify contaminated soil.
[0042] Phytoremediation technology: using plants to remove, transform and destroy pollutants in the soil through extraction, rhizosphere filtration, volatilization and fixation.
[0043] Barrier landfill technology: placing contaminated soil in an impermeable barrier landfill or laying a barrier layer to block the migration and diffusion of pollutants.
[0044] Natural attenuation technology: Reduce the quantity, toxicity and mobility of pollutants in groundwater and soil to an acceptable risk level based on the naturally occurring physical, chemical and biological effects of the site.
[0045] Multiphase extraction technology: vacuum extraction is used to extract soil gas, groundwater, and floating oil from underground contaminated areas to the ground for phase separation and treatment.
[0046] Soil vapor extraction technology: supply air or oxygen to the soil, rely on the aerobic activity of microorganisms to promote the degradation of pollutants, and use the pressure gradient in the soil to force volatile organic compounds and degradation products to flow to the extraction well to be extracted and removed.
[0047] As an implementable method that has been discovered in the field. At present, there are many preparation processes for zirconium-based oxides as adsorbents, but the specific surface area of zirconium-based oxides prepared in the prior art needs to be improved. For example, a nanoporous zirconium oxide adsorbent prepared by Taiyuan University of Science and Technology uses an organic zirconium source as a precursor, a long-chain aliphatic dicarboxylic acid dodecanedioic acid as a dispersant, hexadecyl ammonium bromide as a cationic template, and an ethanol aqueous solution as a reaction system. Under weak acid conditions, a solvent volatilization self-assembly reaction is carried out to form a zirconium-containing wet gel, which is then calcined at high temperature to prepare a zirconium oxide adsorption material. The specific surface area of the zirconium-based oxide adsorbent prepared by this process is 90.2 to 106.3 m 2 / g.
[0048] As an implementable method that has been discovered in the art. For another example, China Petrochemical Corporation discloses a spherical zirconium oxide adsorbent and its preparation method and application, which includes adding an organic ammonium salt and an organic zirconium precursor to a mixed solution of glacial acetic acid and formic acid, and then adding water thereto, transferring the mixed solution to a closed reactor, and reacting at a constant temperature of 160°C to 220°C for 12 to 48 hours, cooling, separating the solid product, washing, drying, and then roasting. The spherical zirconium oxide adsorbent prepared by the present invention has a diameter of 200 to 400 nm, and is distributed with mesopores with a diameter of 1 to 10 nm. The spherical adsorbent is a sphere formed by self-assembly of zirconium oxide nanocrystals with a unit size of 5 to 10 nm; the specific surface area of the adsorbent prepared by this process is 100 to 250 m 2 / g.
[0049] As an implementable method that has been discovered in the art. There are also some zirconium-based oxides doped with other elements, such as a zirconium-based nitrogen oxide adsorbent, wherein the adsorbent is a composite oxide with zirconium oxide as the main component and containing two modifying elements, silver and manganese, wherein the molar percentages of silver and manganese are: silver is 2-10%, manganese is 5-50%, and the balance is zirconium oxide; the composite oxide is a tetragonal composite oxide with a specific surface area of 80-250m2 / g prepared by impregnation, precipitation or microemulsion. The adsorbent material of this technology can be prepared in any known way, among which the better method is: the adsorbent containing manganese and zirconium can be prepared by coprecipitation and microemulsion; the adsorbent containing silver, manganese and zirconium can be obtained by equal volume impregnation, by impregnating the adsorbent material containing manganese and zirconium prepared above with silver nitrate solution; the adsorbent containing silver, manganese and zirconium can also be prepared by coprecipitation or microemulsion. The adsorption performance evaluation of nitrogen oxides is carried out according to the following steps: the above solid adsorbent is placed in a thermogravimetric analyzer in a flow state, the concentration of nitrogen oxides in the air flow is several to 5000ppm, the oxygen concentration is 0-20%, and the remaining balance gas is nitrogen; the change value of the weight gain of the adsorbent at a specified temperature over time is detected by thermogravimetric analysis to obtain the adsorption curve of the adsorbent; when the weight gain does not change significantly over time, saturated adsorption is reached, and the weight gain obtained at this time is recorded as the equilibrium adsorption amount, which is expressed by the mass of nitrogen oxides adsorbed per gram of adsorbent; the time for the adsorbent of the present invention to reach the equilibrium adsorption amount is generally within 10-120 minutes; after the adsorbent of the present invention reaches saturated adsorption, the adsorbent can be heated to 250-600°C in an inert atmosphere or a reducing atmosphere to release or react the adsorbed nitrogen oxides and convert them into nitrogen before further use. From the weight loss curve of the thermogravimetric analyzer, the desorption amount of the gas can be detected and the complete desorption temperature can be determined. In an actual exhaust gas environment, such as flue gas or exhaust gas from an internal combustion engine, water vapor often coexists with nitrogen oxides. Therefore, in the present invention, by simultaneously introducing water and nitrogen oxides into a carrier gas, an experiment was conducted to investigate the adsorption of nitrogen oxides by the adsorbent material in water vapor. During the experiment, the volume content of water vapor was 1-10%. This type of material has a good ability to resist competitive adsorption with water. Features of the present invention: The adsorbent does not contain platinum group precious metals, but is a composite oxide containing zirconium, manganese and silver, etc. It is an adsorbent material with a high specific surface area, and its specific surface area is 80-250m 2 / g.
[0050] As an implementable method that has been discovered in the art. A method for preparing a high-strength pectin zirconium hydroxide microsphere adsorbent comprises the following steps: 1) zirconium hydroxide powder, diammonium bicarbonate, and polyethylene glycol are mixed, and deionized water is added, and the mixed solution is ultrasonically made to form a uniformly dispersed suspension; 2) deionized water is added to the pectin and stirred until the pectin is completely dissolved; 3) the suspension obtained in step 1) is added to the pectin solution in step 2), and stirred evenly at 80-95°C to obtain a white gel liquid; 4) the white gel liquid obtained in step 3) is added dropwise to dimethyl silicone oil through a dropper, and the white particles under the dimethyl silicone oil are filtered, washed, and vacuum dried to obtain a pectin zirconium hydroxide microsphere adsorbent. Improved, the mass ratio of the zirconium hydroxide powder, diammonium bicarbonate, polyethylene glycol, and pectin is 100:1-5:0.1-0.5:10-30. In step 2), when deionized water is added to the pectin, it is stirred at 25-45°C for 2-3 hours until it dissolves. As a further improvement of the technical solution of the preparation method of the present invention, in step 4), the particle size of the obtained pectin zirconium hydroxide microsphere adsorbent is 0.6-1.2 mm. In step 4), the vacuum drying condition is vacuum drying at a temperature of 60-80° C. for 6-10 hours. The diammonium bicarbonate can be replaced by ammonium bicarbonate or ammonium carbonate. The molecular weight of the polyethylene glycol is 2000-6000.
[0051] However, the specific surface area of the adsorbent material prepared by the above technology needs to be improved. In order to further increase the specific surface area of the adsorbent and improve the adsorption effect, the embodiment of the present invention discloses a method for preparing a zirconium-based oxide adsorbent material, comprising the following steps:
[0052] 1) Dissolving: dissolving 1-5 g ZrOCl2·8H2O in 10-50 mL ultrapure water at a stirring speed of 100-300 r / min, and then adding Ce(NO3)3·6H2O and Fe(NO3)3 according to a Zr:Ce:Fe molar ratio of 100:(3-6):(8-12) to obtain a composite zirconium salt precursor solution;
[0053] 2) High-pressure reaction: the composite zirconium salt precursor solution is transferred into a high-pressure reactor, and the high-pressure reactor is placed in an oven and heated to 160-220° C. at a rate of 10-40° C. / min for 8-12 hours;
[0054] 3) Washing: After cooling naturally to room temperature, centrifuge to remove the supernatant to obtain the precipitate, and rinse the precipitate with ultrapure water 2 to 5 times;
[0055] 4) Calcination: The precipitate is dried at 60-80° C. for 5-10 h, and then calcined at 240-350° C. for 3-6 h in an air atmosphere to obtain a zirconium-based oxide adsorbent.
[0056] In a preferred embodiment, the optimal dosage ratio of the composite zirconium salt precursor solution in step 1) is 1-2 g ZrOCl2·8H2O added to 10-25 mL ultrapure water.
[0057] The reaction carried out in the autoclave is a hydrothermal reaction. The purpose of the hydrothermal reaction is to obtain nano-particle products while causing the adsorbent material to undergo a reduction reaction, so as to increase its specific surface area and provide favorable conditions for adsorbing pollution source ions. In a preferred embodiment, the optimal high-pressure reaction conditions in step 2) are to increase the temperature to 200°C at a rate of 30°C / min and maintain for 10 hours.
[0058] In a preferred embodiment, the precipitate after centrifugation in step 3) is washed three times with ultrapure water to achieve the required purity.
[0059] The purpose of drying is to remove moisture to avoid the adverse effect of moisture on the morphology of the adsorbent during the subsequent high-temperature calcination process, so the temperature of the drying process should not be too high or too low. Too high a temperature will cause partial oxidation, and too low a temperature will cause the moisture to be removed too slowly or volatilize incompletely. In a preferred embodiment, the optimal drying conditions in step 4) are 60-65°C for 6-8h. As an example, the drying condition is drying at 60°C for 8h.
[0060] The purpose of calcination is to obtain metal oxides. In a preferred embodiment, the best calcination condition in step 4) is to increase the temperature to 300° C. at a rate of 30° C. / min and calcine for 4 to 5 hours in an air atmosphere.
[0061] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0062] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0063] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0064] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0065] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0066] The raw materials in the examples of the present invention were all obtained through commercial sources.
[0067] Example 1
[0068] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0069] Under magnetic stirring, 1.5 g ZrOCl2·8H2O solid was dissolved in 20 mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶3∶12. Then the mixture was transferred to a 50 mL high pressure reactor, heated to 200°C at a heating rate of 30°C / min, maintained at 200°C for 10 h, and after natural cooling, the solid and liquid were separated by centrifugation. The solid was washed with ultrapure water three times, dried in a 60°C oven for 8 h, and finally calcined at 300°C for 4 h in a muffle furnace (air atmosphere). After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0070] The scanning electron micrograph of the zirconium-based oxide adsorbent is shown in Figure 1 ,Depend on Figure 1 It can be seen that the zirconium-based oxide adsorption material prepared in this embodiment is nano-scale particles with a rough surface.
[0071] Figure 4 is the N2 adsorption-desorption curve of the zirconium-based oxide adsorbent material prepared in this example, Figure 4 It can be seen that the specific surface area of the zirconium-based oxide adsorbent prepared in this embodiment is as high as 385 m 2 / g, and the pore size is about 9.8nm. This large specific surface area provides favorable conditions for fully exerting its adsorption performance.
[0072] Example 2
[0073] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0074] Under the action of magnetic stirring, 1.5g ZrOCl2·8H2O solid was dissolved in 20mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶5∶12, and then transferred to a 50mL high-pressure reactor, heated to 200℃ at a heating rate of 30℃ / min, maintained at 200℃ for 10h, and after natural cooling, the solid and liquid were separated by centrifugation, the solid was washed with ultrapure water 3 times, the solid was dried in a 60℃ oven for 8h, and finally placed in a muffle furnace and calcined at 300℃ for 4h (air atmosphere), and the zirconium-based oxide adsorption material was obtained after natural cooling.
[0075] Example 3
[0076] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0077] Under the action of magnetic stirring, 1.5g ZrOCl2·8H2O solid was dissolved in 20mL ultrapure water, and CeN3O9·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶6∶12. Then the mixture was transferred to a 50mL high-pressure reactor, heated to 200℃ at a heating rate of 30℃ / min, maintained at 200℃ for 10h, and after natural cooling, the solid and liquid were separated by centrifugation. The solid was washed with ultrapure water 3 times, dried in a 60℃ oven for 8h, and finally calcined at 300℃ for 4h in a muffle furnace (air atmosphere). After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0078] Example 4
[0079] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0080] Under magnetic stirring, 1.5 g ZrOCl2·8H2O solid was dissolved in 20 mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the molar ratio of Zr:Ce:Fe of 100:5:8. The mixture was then transferred to a 50 mL high pressure reactor and heated to 200°C at a heating rate of 30°C / min. The mixture was maintained at 200°C for 10 h. After natural cooling, the solid and liquid were separated by centrifugation, the solid was washed three times with ultrapure water, and the solid was dried in a 60°C oven for 8 h. Finally, the solid was placed in a muffle furnace and calcined at 300°C for 4 h (in air atmosphere). After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0081] Example 5
[0082] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0083] Under magnetic stirring, 1.5 g ZrOCl2·8H2O solid was dissolved in 20 mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶5∶10. Then the mixture was transferred to a 50 mL high pressure reactor and heated to 200°C at a heating rate of 30°C / min. The mixture was maintained at 200°C for 10 h. After natural cooling, the solid and liquid were separated by centrifugation, and the solid was washed with ultrapure water three times. The solid was dried in a 60°C oven for 8 h, and finally calcined at 300°C for 4 h (in air atmosphere) in a muffle furnace. After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0084] Example 6
[0085] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0086] Under the action of magnetic stirring, 1.5g ZrOCl2·8H2O solid was dissolved in 20mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶5∶12. Then it was transferred to a 50mL high-pressure reactor, heated to 200℃ at a heating rate of 30℃ / min, maintained at 200℃ for 10h, and after natural cooling, the solid and liquid were separated by centrifugation, the solid was washed with ultrapure water 3 times, the solid was dried in a 60℃ oven for 8h, and finally placed in a muffle furnace and calcined at 260℃ for 6h (air atmosphere). After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0087] Example 7
[0088] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0089] Under magnetic stirring, 1.5 g ZrOCl2·8H2O solid was dissolved in 20 mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶5∶12. Then the mixture was transferred to a 50 mL high pressure reactor, heated to 200°C at a heating rate of 30°C / min, maintained at 200°C for 10 h, and after natural cooling, the solid and liquid were separated by centrifugation. The solid was washed with ultrapure water for 3 times, dried in a 60°C oven for 8 h, and finally calcined at 350°C for 3 h (in air atmosphere) in a muffle furnace. After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0090] Comparative Example 1
[0091] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0092] Under the action of magnetic stirring, 1.5g ZrOCl2·8H2O solid was dissolved in 20mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶2∶13. Then the mixture was transferred to a 50mL high-pressure reactor, heated to 200℃ at a heating rate of 30℃ / min, maintained at 200℃ for 10h, and after natural cooling, the solid and liquid were separated by centrifugation. The solid was washed with ultrapure water 3 times, dried in a 60℃ oven for 8h, and finally calcined at 300℃ for 4h in a muffle furnace (air atmosphere). After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0093] Comparative Example 2
[0094] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0095] Under magnetic stirring, 1.5 g ZrOCl2·8H2O solid was dissolved in 20 mL ultrapure water, and Ce(NO3)3·6H2O and Fe(NO3)3 were added according to the Zr∶Ce∶Fe molar ratio of 100∶8∶5. Then the mixture was transferred to a 50 mL high pressure reactor, heated to 200°C at a heating rate of 30°C / min, maintained at 200°C for 10 h, and after natural cooling, the solid and liquid were separated by centrifugation. The solid was washed with ultrapure water for 3 times, dried in a 60°C oven for 8 h, and finally calcined at 300°C for 4 h (in air atmosphere) in a muffle furnace. After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0096] Comparative Example 3
[0097] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0098] Under the action of magnetic stirring, 1.5 g ZrOCl2·8H2O solid was dissolved in 20 mL ultrapure water, then transferred to a 50 mL high-pressure reactor, heated to 200 °C at a heating rate of 30 °C / min, maintained at 200 °C for 10 h, and after natural cooling, the solid and liquid were separated by centrifugation, the solid was washed three times with ultrapure water, the solid was dried in a 60 °C oven for 8 h, and finally placed in a muffle furnace and calcined at 300 °C for 4 h (air atmosphere), and the zirconium-based oxide adsorption material was obtained after natural cooling.
[0099] The XPS graph of the zirconium-based oxide adsorbent prepared in this comparative example is shown in Figure 2 The results show that the material is mainly composed of Zr and O elements. Figure 3 , referring to the PDF card, this material belongs to ZrO2 (00-005-0543).
[0100] Comparative Example 4
[0101] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0102] Under the action of magnetic stirring, 1.5g ZrOCl2·8H2O solid was dissolved in 20mL ultrapure water, and Ce(NO3)3·6H2O was added according to the Zr:Ce molar ratio of 100:5, and then transferred to a 50mL high-pressure reactor, heated to 200℃ at a heating rate of 30℃ / min, maintained at 200℃ for 10h, and after natural cooling, the solid and liquid were separated by centrifugation, the solid was washed with ultrapure water 3 times, and the solid was dried in a 60℃ oven for 8h. Finally, it was placed in a muffle furnace and calcined at 300℃ for 4h (air atmosphere). After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0103] Comparative Example 5
[0104] A zirconium-based oxide adsorption material, the preparation method is as follows:
[0105] Under the action of magnetic stirring, 1.5g ZrOCl2·8H2O solid was dissolved in 20mL ultrapure water, and Fe(NO3)3 was added according to the Zr:Fe molar ratio of 100:12. Then the mixture was transferred to a 50mL high-pressure reactor and heated to 200℃ at a heating rate of 30℃ / min. The temperature was maintained at 200℃ for 10h. After natural cooling, the solid and liquid were separated by centrifugation, and the solid was washed with ultrapure water for 3 times. The solid was dried in a 60℃ oven for 8h and finally calcined at 300℃ in a muffle furnace for 4h (air atmosphere). After natural cooling, the zirconium-based oxide adsorption material was obtained.
[0106] Application Example 1 (Determination of the removal efficiency of the zirconium-based oxide adsorbent material of Example 1 for arsenic, fluorine, selenium and chromium)
[0107] Weigh several portions of 20 mg of the zirconium-based oxide adsorbent material prepared in Example 1 above, and add them to 40 mL of a solution with an initial arsenic, fluorine, selenium, and chromium concentration of 5 mg / L in sequence, and the background solution is 0.04 mol / L of sodium chloride. Use sodium hydroxide solution or hydrochloric acid to adjust the pH of the solution to 7, wrap the container with aluminum foil to avoid light, place it on a rotary shaker, react for 48 hours, and separate the solid and liquid by high-speed centrifugation. The liquid is filtered through a 0.22 μm filter membrane, acidified with nitric acid, and the amount of arsenic, selenium, and chromium in the solution is measured by inductively coupled plasma emission spectroscopy (ICP-OES), and the fluorine content in the solution is measured by a fluoride ion electrode, and the removal efficiency of zirconium-based oxide for arsenic, selenium, chromium, and fluorine is calculated.
[0108] The removal efficiency of the adsorbent material of Example 1 for arsenic, fluorine, selenium and chromium is shown in Figure 5The results show that except for the lower removal rate of Cr(III), the removal rates of F, Se(IV), Se(VI), As(III), As(V), and Cr(VI) are all higher than 95%.
[0109] Application Example 2 (Adsorption performance of zirconium-based oxides for arsenic and fluorine)
[0110] Weigh several portions of 20 mg of the adsorbent prepared in Example 1 above, and add them to 40 mL of a solution with an initial arsenic concentration of 0 to 500 mg / L or an initial fluorine concentration of 0 to 200 mg / L, and the background solution is 0.04 mol / L sodium chloride. Use sodium hydroxide solution or hydrochloric acid to adjust the pH of the solution to 7, wrap the container with aluminum foil to avoid light, place it on a rotary shaker, react for 48 hours, and separate the solid and liquid by high-speed centrifugation. The liquid is filtered through a 0.22 μm filter membrane, acidified with nitric acid, and the amount of arsenic in the solution is measured by inductively coupled plasma emission spectroscopy (ICP-OES), and the fluorine content in the solution is measured by a fluoride ion electrode. The maximum adsorption capacity of zirconium-based oxides for arsenic and fluorine is obtained by fitting the Langmuir model.
[0111] Application Example 3 (Adsorption performance of zirconium-based oxides on selenium)
[0112] Weigh several portions of 20 mg of the adsorbent prepared in Example 1 above, and add them sequentially to 40 mL of a solution with an initial selenium concentration of 0 to 500 mg / L, and the background solution is 0.04 mol / L sodium chloride. Use sodium hydroxide or hydrochloric acid to adjust the pH of the solution to 5, wrap the container with aluminum foil to avoid light, place it on a rotary shaker, react for 48 hours, and separate the solid and liquid by high-speed centrifugation. The liquid is filtered through a 0.22 μm filter membrane, acidified with HNO3, and the amount of selenium in the solution is measured by inductively coupled plasma emission spectroscopy (ICP-OES), and the maximum adsorption capacity of zirconium-based oxides for selenium is obtained by Langmuir model fitting.
[0113] The adsorption isotherms and Langmuir fitting results of the zirconium-based oxide adsorbent material of Example 1 for arsenic, fluorine and selenium are shown in Figure 6 The data show that the maximum adsorption capacity of zirconium-based oxide adsorbent materials for fluorine, arsenic and selenium are 25.5 mg F / g, 80.7 mg As(III) / g, 43.7 mg As(V) / g, 82.0 mg Se(IV) / g and 45.7 mg Se(VI) / g, respectively.
[0114] The adsorption performance of the zirconium-based oxide adsorbent materials prepared in Examples 2-7 and Comparative Examples 1-5 for various ions was measured using the methods of Application Examples 3 and Application Examples 4. The results are shown in Table 1.
[0115] Table 1 Adsorption capacity of various ions of zirconium-based oxide adsorbent materials prepared in Examples 2-7 and Comparative Examples 1-5 (mg / g)
[0116] As(III) As(V) Se(IV) Se(VI) F Example 2 81.3 42.9 80.9 43.9 25.7 Example 3 79.6 41.6 83.6 46.1 24.6 Example 4 80.6 43.2 81.3 45.3 24.8 Example 5 81.4 42.7 83.2 44.8 25.4 Example 6 78.9 41.8 82.4 46.9 23.9 Example 7 80.7 44.1 79.8 45.5 26.1 Comparative Example 1 68.9 35.9 60.8 36.8 20.3 Comparative Example 2 67.6 37.8 67.2 34.9 20.9 Comparative Example 3 59.8 34.2 55.3 30.2 16.7 Comparative Example 4 63.6 35.1 59.6 32.1 18.1 Comparative Example 5 62.8 35.4 60.4 31.9 17.9
[0117] As can be seen from Table 1, in Comparative Examples 1 and 2, due to the adjustment of the dosage ratio of iron and cerium, the adsorption capacity of the obtained zirconium-based oxide adsorbent for the five ions is reduced. It can be seen that the ratio of iron oxide and cerium oxide in the adsorbent is very important for promoting zirconium oxide to adsorb pollution source ions. Comparative Examples 3-5 omit the compounding of iron and / or cerium, and the adsorption effect of the prepared adsorbent on the five ions is further reduced. Comparative Examples 1-5 fully illustrate that there is a certain synergistic effect between zirconium oxide, iron oxide and cerium oxide.
[0118] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a zirconium-based oxide adsorption material, characterized in that: The method comprises the following steps: using a mixed solution of zirconium oxychloride, cerium salt and iron salt as a precursor, obtaining a precipitate through a high-pressure hydrothermal reaction, and preparing the zirconium-based oxide adsorption material after washing and calcining the precipitate after centrifugation; Wherein, the molar ratio of the zirconium oxychloride, the cerium salt and the iron salt is 100:(3-6):(8-12).
2. The method for preparing a zirconium-based oxide adsorption material according to claim 1, characterized in that: The molar ratio of the zirconium oxychloride, the cerium salt and the iron salt is 100:(5-6):(9-10).
3. The method for preparing a zirconium-based oxide adsorbent material according to claim 1, characterized in that: The conditions of the high-pressure hydrothermal reaction are: temperature 160-210° C., time 8-12 h, and heating rate 10-40° C. / min.
4. The method for preparing a zirconium-based oxide adsorbent material according to claim 3, characterized in that: The conditions of the high pressure hydrothermal reaction are: temperature 200° C., time 10 h, and heating rate 30° C. / min.
5. The method for preparing a zirconium-based oxide adsorbent material according to claim 1, characterized in that: The calcination conditions are: first drying at 60-80° C. for 6-10 hours, and then calcining at 260-350° C. for 3-6 hours.
6. The method for preparing a zirconium-based oxide adsorbent material according to claim 5, characterized in that: The calcination temperature is 300° C. and the calcination time is 4 hours.
7. The method for preparing a zirconium-based oxide adsorbent material according to claim 1, characterized in that: The calcination atmosphere is air atmosphere.
8. A zirconium-based oxide adsorption material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the zirconium-based oxide adsorbent material as claimed in claim 8 for adsorbing and removing heavy metal, selenium, arsenic or fluorine pollution in groundwater, surface water or industrial wastewater.
10. The use according to claim 9, characterized in that The heavy metal is cadmium.
Citation Information
Patent Citations
Preparation methods for granular titanium dioxide and lanthanum-loaded granular titanium dioxide
CN107746073A
Zirconium-based arsenic removing material and preparation method and application thereof
CN102068957A
Cerium-zirconium composite oxide and preparation method thereof
CN114433063A
Preparation method of ceria-zirconia-based oxide
JP2006256911A
High capacity adsorbent for oxyanions and cations and method for making the same
US20200254438A1